Avaliação da ocorrência de microplásticos em moluscos heterobrânquios marinhos da Costa Atlântica Nordestina do Brasil e da Costa do Pacífico Central de El Salvador - Flores, Gina Leonor Lopez (2021)
The record of contamination by microplastics that exists in the marine environment is large, and because of that it is important to detect the presence of these particles in the different species that inhabit the marine-coastal ecosystem, to later study what are the possible effects they cause on them. Some of those negative effects already studied in some organisms are problems in the swimming system, slowing down the swimming process, obstruction of the digestive system and reproductive problems. Among these marine animals, mollusks have already been studied, but not all groups of mollusks have been investigated. Therefore, this work addresses for the first time the presence and quantification of microplastics in the digestive tract of marine heterobranchs, a group of mollusks with ecological and socioeconomic importance. This study was carried out on beaches in the Atlantic Ocean of Brazil and the Pacific coast of El Salvador, with the main objective of comparing the ingestion of microplastic by sea slugs from both sites, without being relevant the place of collection due to the fact that it is known that there is a record of microplastic contamination in both oceans. The presence of microplastics was confirmed for the first time in marine heterobranchs from both oceans, being a total of 2,577 microplastic particles in their digestive tract. The morphological characterization of the particles was carried out, studying their distribution by type, color and size. Microplastic particles were registered, but also macroplastic particles, with a low amount of 27 particles, in contrast to the total microplastic quantified in this work.